Graded simple Jordan superalgebras of growth one - Kac, Victor G., 1943- (Memoirs of the American Mathematical Society, 2001)
Introduction Structure of the even part Cartan type Even part is direct sum of two loop algebras $A$ is a loop algebra $J$ is a finite dimensional Jordan superalgebra or a Jordan superalgebra of a superform The main case Impossible cases Bibliography.